2009
DOI: 10.1007/s00167-009-0904-z
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder activity level in the preoperative assessment of patients with rotator cuff tears

Abstract: The purpose of this study was to investigate shoulder activity level in preoperative assessment of shoulder function and health-related quality of life (QoL) for patients with rotator cuff tears. One hundred and six patients with rotator cuff tears were prospectively evaluated using the following outcome instruments: the Shoulder Activity scale, the Constant scale, the Simple Shoulder Test, and the Short Form-36v2 (SF-36v2). Clinical and structural data, including patients' demographics, comorbidities, duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In addition, the Shoulder Activity Level was the primary activity level score outcome examined in this study since it is a validated, patient-determined outcome score that can be used to measure a patient’s activity level. 19 , 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the Shoulder Activity Level was the primary activity level score outcome examined in this study since it is a validated, patient-determined outcome score that can be used to measure a patient’s activity level. 19 , 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…Patient-reported outcomes measures have become an important component of determining patient outcomes after sports-related injuries treated both surgically and nonsurgically. 2 , 4 , 5 , 8 , 9 , 13 , 15 , 16 , 18 , 20 - 22 , 24 , 25 , 28 An important component of patient-reported outcomes measures is the baseline activity level of a patient, which is in effect a functional measure of musculoskeletal health. It is important to be able to quantify a patient’s activity level so it can be evaluated within a context of other patients for both research needs and for comparison with population normative data when treating injuries.…”
mentioning
confidence: 99%
“…Because the activity scale is designed to measure patients' overall level of activity, patients are asked to indicate how often they performed each activity during their healthiest and most active state in the previous year. Previous studies using the SAS have shown its reliability, validity, and responsiveness [4,5,19]. Among subjects with no history of shoulder symptoms or treatment for a shoulder condition, the shoulder activity score decreases with age and is lower in women than men [13].…”
Section: Methodsmentioning
confidence: 97%
“…Among subjects with no history of shoulder symptoms or treatment for a shoulder condition, the shoulder activity score decreases with age and is lower in women than men [13]. In patients with shoulder disorders, the shoulder activity score is highest in patients with shoulder instability, intermediate in patients with rotator cuff disease, and lowest in patients with shoulder osteoarthritis [19]. In addition, patients are asked two multiple-choice questions regarding level of sports participation (without organized officiating, with organized officiating, or at a professional level) in contact and overhead-throwing sports.…”
Section: Methodsmentioning
confidence: 99%